2005
DOI: 10.17796/jcpd.28.2.g45173lp7661g078
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic alternative for fluorosis blemishes with the usage of a dual bleaching system based on hydrogen peroxide at 35%

Abstract: Esthetic dental procedures in pediatric dentistry represent sources of satisfaction and realization, as much for the patient as for the professional. Lack of dental esthetics may develop psychological problems in infant as well as in adolescent patients. Blemishes produced by fluorosis appear as a challenge to the pediatric dentist and alternatives for treatment are desired. The scope of this present paper is to relate a clinical case with esthetic solution for blemishes in teeth enamel due to fluorosis. A dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…The ability to study fl uorosis longitudinally may enable treatment modalities to be assessed. For example two common means of reducing the aesthetic impact of fl uorosis are microabrasion (to remove the affected enamel) and peroxide bleaching (to harmonize tooth shade) [Akpata, 2001;Allen et al, 2004;Bussadori et al, 2004;Huckabee, 2001;Loyola-Rodriguez et al, 2003;Lynch and McConnell, 2003]. The duration of application and concentration of the actives in each of these systems has not been accurately determined in relation to fl uorosis and the technique described in the current work may be a possible solution.…”
Section: Comparison With Tf Indexmentioning
confidence: 98%
“…The ability to study fl uorosis longitudinally may enable treatment modalities to be assessed. For example two common means of reducing the aesthetic impact of fl uorosis are microabrasion (to remove the affected enamel) and peroxide bleaching (to harmonize tooth shade) [Akpata, 2001;Allen et al, 2004;Bussadori et al, 2004;Huckabee, 2001;Loyola-Rodriguez et al, 2003;Lynch and McConnell, 2003]. The duration of application and concentration of the actives in each of these systems has not been accurately determined in relation to fl uorosis and the technique described in the current work may be a possible solution.…”
Section: Comparison With Tf Indexmentioning
confidence: 98%
“…Previous reports on the use of Hi-L have indicated that the pH falls to as low as 4.0 immediately after action and that the teeth are susceptible to demineralization by acid after bleaching, suggesting the possibility of demineralization 13) . However, in the present study, demineralization findings were not evident; rather findings resembling crystal growth were observed.…”
Section: ) Hr-tem Observationmentioning
confidence: 95%
“…In some parts, crystal growth toward the a-axis were observed (Figures 3-c,d). On the one hand the crystal gaps were slightly wider than in control Discussion Tooth whitening is achieved by a masking effect 13) achieved by producing micro changes such as roughness on the superficial layer of the enamel causing diffuse light reflection to cover up the internal color, and by a bleaching effect 14) achieved by decomposing the colored molecules with free radicals generated on the superficial layer of enamel.…”
Section: ) Hr-tem Observationmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been demonstrated that white spots match better with the remaining tooth structure following the bleaching procedures. [5][6][7][8] Knosel et al 8) found that bleaching could satisfactorily camouflage white spot lesions observable following fixed orthodontic therapy. The bleaching treatment may have additional advantages in orthodontically treated subjects as they are usually affected with various degrees of discoloration in healthy and demineralized parts of the dentition.…”
Section: Introductionmentioning
confidence: 99%